Epidemiological, clinical, and laboratory features of patients infected with Elizabethkingia meningoseptica at a tertiary hospital in Hefei City, China - Li, Yajuan; Liu, Tingting; Shi, Cuixiao; Wang, Bo; Li, Tingting; Huang, Ying; Xu, Yuanhong; Tang, Ling (Frontiers in Public Health, 2022)
Background: Elizabethkingia meningoseptica is a bacterium causing potential nosocomial infections and is associated with a high mortality rate; however, the date of patients in the Hefei population who have been diagnosed with this infection are generally limited. Purpose: The clinical and laboratory data of patients from a tertiary hospital in Hefei City who had Elizabethkingia meningoseptica infection were evaluated in this retrospective analysis. Patients and methods: From May 2017 to November 2021, there were 24 patients infected with Elizabethkingia meningoseptica in the First Affiliated Hospital of Anhui Medical University. Data were gathered from the hospital's electronic medical records for all patients. Results: The most prevalent symptom among the 24 patients was fever (83.3%), followed by edema (41.7%), cough (37.5%), altered consciousness (41.7%), sputum (37.5%) and laboratory results presented with anemia (75%), hypoproteinemia (75%), elevated C-reactive protein (CRP) (66.7%), neutrophilia (54.2%), and leukocytosis (50.0%). Hepatic disease (1 vs 7, P = 0.009) was the only significant risk factor of underlying diseases. The mean value of lymphocyte (LYMPH#) (1.4 vs 0.83×〖10 〗^9/L, P = 0.033) counts was higher in survival group than death group, while both anemia (8 vs 10, P = 0.024) and hypoproteinemia (8 vs 10, P = 0.024) occurred more frequently in the death group compared with the survival one. Conclusion: Fever was the most common symptom and the only significant factor of underlying diseases was hepatic disease (P = 0.009) which often occurred in death groups. In the current investigation, the risk factors for death in patients were anemia, hypoproteinemia and lymphocyte count. The susceptibility of some quinolones, piperacillin-tazobactam and cotrimoxazole was relatively high, suggesting that they may be the preferred drugs for the treatment of Elizabethkingia meningoseptica infection. As Elizabethkingia meningoseptica can produce biofilm to pollute the hospital environment and cause infection of patients, the disinfection of hospital environment should be strengthened and medical staff should pay attention to aseptic operation.